Cirrhosis-related ascites with right heart failure and pulmonary tuberculosis - Putra, Agus Dody Pranata Suadi; Dewi, Dewa Ayu Rina Wiana; Wirawan, I. Made Suma (International Journal of Advances in Medicine, 2022)
Ascites is defined as an excess of fluid within the peritoneal cavity. Causes of ascites may be classified into two pathophysiologic categories: associated with the normal peritoneum and occur due to a diseased peritoneum. Ascites is clinically apparent when the patient presents either symptomatically with abdominal distension, thus leading to further testing, or asymptomatically when radiological imaging shows unexpected peritoneal fluid accumulation. The serum ascites-albumin gradient (SAAG) and total protein levels from ascitic fluid are useful to distinguish the etiology of ascites. We report a case of a 30-years-old man with shortness of breath, the stomach has been getting bigger, nausea, and cough which was subsequently diagnosed with cirrhosis-related ascites accompanied with right heart failure and pulmonary tuberculosis.